Mereduksi Radikalisme Mahasiswa Berbasis Nilai-Nilai Multikultural di Perguruan Tinggi Islam - Amru Almu'tasim (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Radical Islamic groups began to create a cadre base in college, the change movement this group performed a select group of students as new agents that are considered capable of changing patterns of movement. The rising tide of Islamic radical groups among the students can not be separated from the regeneration efforts of intellectuals among Islamic fundamentalists. The strategy does is to make students indokrinasi ideological hard to part from this group. This phenomenon eventually form a new metamorphosis of the radical Islamic movement on campus. With cultivate Islamic studies and nuanced action multicultural values radicalism and fundamentalism virus can at least be reduced.Keyword. Radical, College, Multicultural Values